PELATIHAN MIKROKONTROLLER BAGI PEMUDA ANCOL KABUPATEN CIAMIS - Nurdiansyah, Rian; Busaeri, Nundang; Permana, Prama (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Youth have an important role in development, where young people are required to have an important role in the welfare of society. In the current era of development, the role of technology has become something important to improve development. However, in reality in society, many people think that this technology can only be used by highly educated people, where people in general are only users and even spectators in the development of this technology. The Ancol Youth Association (IMA) is a youth group located in Ancol Hamlet, Sindangkasih Village, Sindangkasih District, Ciamis Regency which has a high level of teamwork and mutual cooperation to provide a positive impact in society. If this capital is not utilized properly, then the role of youth in the application of technology, especially Appropriate Technology (TTG), will become less useful. Based on the results of initial observations made, these young people still think that technology is something that is considered expensive and cannot be developed by everyone. Under these conditions, the PbM-PPIM implementing team felt challenged to change the youth's paradigm in implementing TTG in society by providing direct understanding and training in developing this technology. In general, the implementation of PbM-PPIM activities has been completed regarding training and implementation of microcontroller-based technology. The effectiveness of the activity was felt to be very good, which was obtained based on the results of interviews with partners that this form of training activity had a very big impact on the partners. This is proven by the increasing knowledge and experience of partners in using microcontroller-based technology.